2020
DOI: 10.1128/mbio.00010-20
|View full text |Cite
|
Sign up to set email alerts
|

A Simple, Cost-Effective, and Robust Method for rRNA Depletion in RNA-Sequencing Studies

Abstract: The profiling of gene expression by RNA sequencing (RNA-seq) has enabled powerful studies of global transcriptional patterns in all organisms, including bacteria. Because the vast majority of RNA in bacteria is rRNA, it is standard practice to deplete the rRNA from a total RNA sample such that the reads in an RNA-seq experiment derive predominantly from mRNA. One of the most commonly used commercial kits for rRNA depletion, the Ribo-Zero kit from Illumina, was recently discontinued abruptly and for an extended… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(57 citation statements)
references
References 13 publications
0
49
0
Order By: Relevance
“…In the latter approach, DNA oligos complementary to rRNA facilitate their removal prior to library construction. These oligos can be biotinylated for magnetic bead affinity purification ( 6 , 22 , 23 ), commercialized for some taxa in the Ribo-Minus and the now discontinued Ribo-Zero Gold kits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter approach, DNA oligos complementary to rRNA facilitate their removal prior to library construction. These oligos can be biotinylated for magnetic bead affinity purification ( 6 , 22 , 23 ), commercialized for some taxa in the Ribo-Minus and the now discontinued Ribo-Zero Gold kits.…”
Section: Introductionmentioning
confidence: 99%
“…Antisense oligos can be used in conjunction with RNaseH to digest DNA–rRNA hybrids ( 5 , 24 ). Several studies in both mammals and bacteria have shown that RNaseH-mediated rRNA depletion is efficient, resulting in sequencing libraries with minimal rRNA derived reads ( 5 , 23–27 ). Commercial solutions have emerged for select taxa; however, the ease of this method allows it in principle to be readily adapted to any taxon, with the primary challenge being the design and acquisition of the 50 nt oligos that tile the specific rRNA sequences encoded in its transcriptome.…”
Section: Introductionmentioning
confidence: 99%
“…DSN has been applied successfully for the sequencing of RNA viruses in complex matrices (Schuh et al, 2020 ; Zhou et al, 2020 ). For subtractive hybridization, unwanted rRNAs/cDNAs are hybridized to biotinylated DNA or Locked nucleic acid ( LNA ) probes and depleted with streptavidin beads (Briese et al, 2015 ; Culviner et al, 2020 ).…”
Section: Approachesmentioning
confidence: 99%
“…Editing e ciency was determined from the raw sequencing chromatograms using the EditR webserver available at http://baseeditr.com/. For RNA-seq analyses, 500 ng of DNase-treated RNA was rRNA-depleted 55 and then used for preparing sequencing libraries with the Illumina TruSeq Stranded total RNA library preparation kit as recommended by the manufacturer. The libraries were sequenced on an Illumina HiSeq4000 sequencer by Novogene.…”
Section: Rna Electromobility Shift Assaysmentioning
confidence: 99%